The politics of strengthening local government: Lessons from Zambia - Resnick, Danielle (International Growth Centre, 2019)
Decentralisation of government functions can improve accountability and service provision, but this pursuit presents key political challenges. Due to greater decentralisation, local governments around the world are increasingly expected to play a major role in tackling key development challenges, from mitigating climate change to improving access to healthy diets. The Sustainable Developments Goals (SDGs) have even reinforced the importance of local government through SDG 11, which strives for inclusive and sustainable cities. Yet, local governments cannot have a transformative role in their communities without sufficient capacity to deliver services and the autonomy to determine local policy priorities. Identifying the constraints to low subnational capacity, and opportunities to surmount them, is therefore critical for local governments to be able to fulfill their potential.